Analysis of Student Needs for Bank Microlearning Development in Biology Learning Media Courses - Diana Susanti; Vivi Fitriani; Rahayu Trisetyowati Untari; Bambang Surpiatno; Riandi Riandi; Rahmi Insanniatul Khairah; Muhammad Yahya (Jurnal Penelitian Pendidikan IPA, 2023)
Biology learning media subject taught about what is media, The function of media, and the operating of media. The material taught has not been conveyed properly because it has not been supported by the right media. This makes students untrained in designing appropriate media for the learning process. This study aims to see the needs of students and lecturers in the development of Microlearning Banks for Biology Learning Media Courses. This researched is a development research using a 4D model. This research was only carried out at the definition stage. This stage was carried out to analyze the needs of student lecturers and in developing Microlearning Banks for Biology Learning Media Courses. Processed data with descriptive analysis. The results of the research analysis show that the needs of students and lecturers for the development of Bank Microlearning for Biology learning media courses were in the required criteria with a percentage of 80% and 83%. It can be concluded that it is necessary to develop Microlearning Banks for Biology learning media courses needed by lecturers and students.